2011
DOI: 10.1029/2011gc003633
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of magnetometry and spectroscopy for identifying magnetofossils in sediments

Abstract: [1] Identification of the mineral remains of magnetotactic bacteria (MTB), known as magnetofossils, is of particular interest because their occurrence can be used for environmental and climatic reconstructions. Single-domain magnetite particles, which are biomineralized in the cell body of MTB, have characteristic properties that can be used to detect their fossil remains. Acquisition of anhysteretic and isothermal remanent magnetization (ARM and IRM), first-order reversal curve (FORC) diagrams, and ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 91 publications
2
48
0
Order By: Relevance
“…Magnetosome chains have remarkable magnetic properties (5,6,9), which have been used to identify bacterial magnetofossils in sediments. Although previous studies demonstrated that observations by electron microscopy and/or magnetic measurements could detect bacterial magnetofossils in natural samples (9)(10)(11)(12)(13), the chain structure is generally lost during sediment aging owing to degradation of organic matter assembling magnetosomes (9,14). This strongly complicates the identification of the bacterial magnetofossils.…”
mentioning
confidence: 83%
“…Magnetosome chains have remarkable magnetic properties (5,6,9), which have been used to identify bacterial magnetofossils in sediments. Although previous studies demonstrated that observations by electron microscopy and/or magnetic measurements could detect bacterial magnetofossils in natural samples (9)(10)(11)(12)(13), the chain structure is generally lost during sediment aging owing to degradation of organic matter assembling magnetosomes (9,14). This strongly complicates the identification of the bacterial magnetofossils.…”
mentioning
confidence: 83%
“… Egli et al [2010] also argued that the selectivity of FORC diagrams for magnetosome detection is unmatched by other magnetic techniques. Several studies have used FORC diagrams to argue for a dominance of sediment magnetic properties by magnetofossils [e.g., Abrajevitch and Kodama , 2009, 2011; Yamazaki , 2008, 2009, 2012; Kind et al , 2011; Roberts et al , 2011a; Larrasoaña et al , 2012], although only the studies of Roberts et al [2011a], Larrasoaña et al [2012], and Yamazaki [2012] have verified this interpretation with TEM observations of magnetic mineral extracts from the analyzed sediments. If magnetosome chains are disrupted and magnetite particles interact magnetostatically, the central ridge in the FORC distributions will be vertically spread, as is evident in the broader outer contours at ∼20 mT in Figure 4.…”
Section: Sources Of Sd Particles In Sedimentsmentioning
confidence: 99%
“…If magnetosome chains are disrupted and magnetite particles interact magnetostatically, the central ridge in the FORC distributions will be vertically spread, as is evident in the broader outer contours at ∼20 mT in Figure 4. Regardless, the presence of SD particles will still be evident in FORC diagrams [e.g., Kind et al , 2011]. Importantly, FORC diagrams enable discrimination of the presence of magnetofossils even when other magnetic minerals are present.…”
Section: Sources Of Sd Particles In Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…asymmetry of the absorption spectra) permit a direct way to detect the anisotropy of magnetosome chains [11,[27][28][29][30][31][32]. Mastrogiacomo et al [33] showed that FMR experiments of MTB using microwave frequency of 4 GHz, i.e.…”
Section: Introductionmentioning
confidence: 99%